Effectiveness of Clinical Nurses' interventions in reducing medication errors in a paediatric ward. Issue 17 (6th July 2020) - Alomari, Albara; Sheppard‐Law, Suzanne; Lewis, Joanne; Wilson, Val
Abstract: Aims and objectives: To evaluate a bundle of interventions, developed and implemented by nurses, to reduce medication administration error rates and improve nurses' medication administration practice. Background: Medication administration errors are a problematic issue worldwide, despite previous attempts to reduce them. Most interventions to date focus on isolated elements of the medication process and fail to actively involve nurses in developing solutions. Design: An Action Research (AR) three‐phase quantitative study. Methods: Phase One aimed to build an overall picture of medication practice. Phase Two aimed to develop and implement targeted interventions. During this phase, the research team recruited six clinical paediatric nurses to be part of the AR Team. Five interventions were developed and implemented by the clinical nurses during this phase. The interventions were evaluated in Phase Three. Data collection included medication incident data, medication policy audits based on hospital medication policy and Safety Attitudes Questionnaire. Quantitative analysis was undertaken. The Standards for QUality Improvement Reporting Excellence (SQUIRE) checklist was followed in reporting this study. Results: Postimplementing the interventions, medication error rates were reduced by 56.9% despite an increase in the number of patient admissions and in the number of prescribed medications. The rate of medication errors per 1, 000 prescribed medications significantly declined from 2014 to 2016. The ward nurses were more compliant with the policy in postintervention phase than preintervention phase. The improvement in SAQ was reported in five of the seven domains. Conclusion: Clinically based nurse's participation in action research enabled practice reflection, development and implementation of a bundle of interventions, which led to a change in nursing practice and subsequent reduction in medication administration error rates. Active engagement of nurses in research empowers them to find solutions that are tailored to their own practice culture and environment.